The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1108/ilds-09-2014-0043
|View full text |Cite
|
Sign up to set email alerts
|

Non-traditional library collections – in digital and other worlds

Abstract: 2014),"Digital collection development for unique users: a veterinary medicine library's approach", Interlending & Document Supply, Vol. 42 Iss 4 pp. 171-175 http://dx.If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Given these reflections on definition, it is more fruitful to talk of traditional and non-traditional materials and collections rather than the libraries as such. In a survey study with public library managers, Michnik and Eriksson (2014) found three main arguments for offering non-traditional collections in libraries.…”
Section: Non-traditional Libraries and Collectionsmentioning
confidence: 99%
“…Given these reflections on definition, it is more fruitful to talk of traditional and non-traditional materials and collections rather than the libraries as such. In a survey study with public library managers, Michnik and Eriksson (2014) found three main arguments for offering non-traditional collections in libraries.…”
Section: Non-traditional Libraries and Collectionsmentioning
confidence: 99%
“…• To attract and engage new patrons, or traditionally hard-to-reach populations, with library collections and services (Edwards, 2018;Michnik & Eriksson, 2014).…”
mentioning
confidence: 99%
“…• To promote an environment of social inclusivity, equal access, and equity (Michnik & Eriksson, 2014;Söderholm, 2015).…”
mentioning
confidence: 99%
See 2 more Smart Citations